3D GEOMETRY RECONSTRUCTION AND STRESS ANALYSIS CAUSED BY STATIC FORCE OF PREMOLAR TOOTH TO SUPPORT ABFRACTION THEORY - FAOLINA (NIM : 13607022); pembimbing : Dr. Ir. Tatacipta Dirgantara; drg. Gantini Subrata, M., ANGGIA
Abfraction is a stress-induced cervical lesion due to an eccentric (lateral) mastication loading. But, many investigators have supported that the etiology of abfraction generally is a multifactorial effect. The aim of this study is to investigate stress distribution in a tooth with a given eccentric mastication loading to support the stress-induced abfraction theory. In this study, the author simulated a second upper premolar in a given eccentric loading using finite element method. The 3D digital geometric model was reconstructed in an image processing software from images of the tooth using the CBCT scan imaging system and processed further in CATIA V5. The 3D tooth geometric model then used as a finite element model, and was studied by simulating a given eccentric static force (200 N) on the palatal cusp 45 degree to the axial axis of the tooth using a finite element software. This study indicate that an eccentric static force show a cervical stress dsitribution in wedge shape form, thus can be used to support the stress-induced theory.